Gender and Ideology in the Spread of Anti-Abortion Policy - Zhang, Amy; Counts, Scott (CHI, 2016)
In the past few years an unprecedented wave of anti-abortion policies were introduced and enacted in state governments in the U.S., affecting millions of constituents. We study this rapid spread of policy change as a function of the underlying ideology of constituents. We examine over 200,000 public messages posted on Twitter surrounding abortion in the year 2013, a year that saw 82 new anti-abortion policies enacted. From these posts,we characterize people’s expressions of opinion on abortion and show how these expressions align with policy change on these issues. We detail a number of ideological differences between constituents in states enacting anti versus pro-abortion policies, such as a tension between the moral values of purity versus fairness, and a differing emphasis on the fetus versus the pregnant woman. We also ﬁnd signiﬁcant differences in how males versus females discuss the issue of abortion, including greater emphasis on health and religion by males. Using these measures to characterize states, we can construct models to explain the spread of abortion policy from state to state and project which types of abortion policies a state will introduce. Models deﬁning state similarity using our Twitter-based measures improved policy projection accuracy by 7.32% and 12.02% on average over geographic and poll-based ideological similarity, respectively. Additionally, models constructed from the expressions of male-only constituents perform better than models from the expressions of female-only constituents, suggesting that the ideology of men is more aligned with the recent spread of anti-abortion legislation than that of women.